Knowledge Management a Tool for Cultural Change in Organizations - Pájaro-Rocha, Jair (EFIM Ediciones, 2022)
This article deals with a review of the bibliography, whose objective is to raise the discussion of Knowledge plays a fundamental role for companies, especially those that base their added value on innovation and especially if it is focused on organisational culture, which is why this article addresses a review of the literature, which aims to raise the discussion of how knowledge management can be used as a tool for change and development in organisations. As a methodology, a review of the theory was developed in order to establish guiding concepts and then develop a reflection on how knowledge management can be used to induce change in the culture of organisations.